2018
DOI: 10.1590/2175-7860201869244
|View full text |Cite
|
Sign up to set email alerts
|

Novas espécies de Manihot (Euphorbiaceae) do Brasil Central

Abstract: ResumoEstudos em herbários e intenso trabalho de campo voltados para abordagens taxonômicas atuais e filogenia do gênero Manihot no cerrado brasileiro possibilitaram a descoberta de cinco novas espécies ocorrentes em áreas de cerrado de Brazlândia (Distrito Federal), Padre Bernardo, Água Fria, São João D'Aliança e Niquelândia (Goiás). Manihot brasiliana, M. congesta, M. incisa, M. pinatiloba e M. porphyrantha são descritas e ilustradas. Características morfológicas dos novos táxones, suas relações com espécies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Floristic and taxonomic studies have shown that species of this genus have problems of taxonomic delimitation due to the lack of taxonomic studies in Brazil. Nonetheless, several new species have been described in recent years (Silva et al 2016;Silva 2016;Silva et al 2017;Mendoza et al 2018), showing significant advances in knowledge of the diversity of the genus. However, little is known about the genetic diversity of these species, especially in the Central-West Region of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Floristic and taxonomic studies have shown that species of this genus have problems of taxonomic delimitation due to the lack of taxonomic studies in Brazil. Nonetheless, several new species have been described in recent years (Silva et al 2016;Silva 2016;Silva et al 2017;Mendoza et al 2018), showing significant advances in knowledge of the diversity of the genus. However, little is known about the genetic diversity of these species, especially in the Central-West Region of Brazil.…”
Section: Introductionmentioning
confidence: 99%